What Can Political Rock Do? A Discussion Based on the Example of the Tom Robinson Band 1976-1979 - John Mullen (Revue Française de Civilisation Britannique)
The Tom Robinson Band had a distinctive approach to political rock music, in their brief career at the end of the nineteen seventies. Neither underground counter-culture nor stadium charity rock, they tried to encourage grassroots involvement in politics as well as to spread their ideas widely, through the pop charts if necessary. This article takes the band as an example to pose the wider question “What Can Political Rock do?”, and develops an approach which puts the concept of the participatory nature of popular music at the centre of the analysis. One of Tom Robinson’s songs was named by Time Out as one of “a hundred songs which changed history”: our article attempts to show why and how this might be the case.